Analisis Status Operasional Transjakarta Rute Pulogadung 2 - Dukuh Atas 2 Akibat Pengoperasian Light Rail Transit (LRT) Jakarta Rute Velodrome - Dukuh Atas - Franciskus, Imanuel; Alvinsyah, Alvinsyah (FSTPT Indonesia, 2024)
The Jakarta LRT construction plan will continue from the Velodrome to Dukuh Atas. However, there is already a Transjakarta Corridor-4 service in the same corridor for the Pulogadung 2- Dukuh Atas 2 route, which has an overlap rate of more than 80%. This study aims to analyze the best policy regarding the operational status of the Transjakarta Pulogadung 2 – Dukuh Atas 2 route when the Jakarta LRT Velodrome – Dukuh Atas route operates based on the preference of Transjakarta users for the LRT tariff plan. Transjakarta user preferences are obtained from the binomial logit model with a utility function built from the stated preference survey results. The utility function was developed using the logistic regression approach through the Spearman correlation test, the Omnibus and Hosmer and Lemeshow feasibility tests, and the validity test using the Root Mean Square Error (RMSE) method. Based on the research analysis, the operational status of Transjakarta will greatly depend on the LRT tariff that will be imposed later. ABSTRAK Rencana pembangunan LRT Jakarta akan dilanjutkan dari Velodrome hingga Dukuh Atas. Namun, saat ini di koridor yang sama sudah ada layanan Transjakarta Koridor-4 rute Pulogadung 2- Dukuh Atas 2 yang tingkat tumpang tindih rutenya lebih dari 80%. Penelitian ini bertujuan untuk menganalisis kebijakan terbaik terkait status operasional Transjakarta rute Pulogadung 2 – Dukuh Atas 2 ketika LRT Jakarta rute Velodrome – Dukuh Atas beroperasi berdasarkan preferensi pengguna Transjakarta terhadap rencana tarif LRT. Preferensi pengguna Transjakarta diperoleh dari model logit binomial dengan fungsi utilitas yang dibangun dari hasil survei stated preference. Fungsi utilitas dikembangkan dengan pendekatan regresi logistik melalui uji korelasi Spearman, uji kelayakan Omnibus dan Hosmer and Lemeshow, dan uji validitas dengan metode Root Mean Square Error (RMSE). Berdasarkan analisis penelitian, status operasional Transjakarta akan sangat tergantung dari besaran tarif LRT yang diberlakukan nanti.